Phytochemical and Antioxidant Activity Evaluation of Lime (Citrus aurantifolia) Juice Powder: Evaluasi Fitokimia dan Aktivitas Antioksidan Serbuk Perasan Jeruk Nipis (Citrus aurantifolia) - Rahmiati, Nur; Sari, Retno; Wahyuni, Tutik Sri (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Many chronic diseases that occur in society can be caused by free radicals. Excessive free radicals in the body can contribute to oxidative stress. Therefore, the role of antioxidants in needed to inhibit the effects of free radicals. Lime (Citrus aurantifolia) is a plant that contains several active compounds. The lime juice was reported to contain flavonoids and ascorbic acid which have several bioactivities including antioxidants. Objectives: This study aims to evaluate the chemical compounds and determine antioxidant activity in the lime juice powder of lime fruit collected from Ujung Pangkah, Gresik. Material and Methods: Lime was squeezed and dried by a freeze-dryer to remove the water content. The phytochemical profile of lime juice powder was evaluated by thin layer chromatography (TLC) method and ascorbic acid content in lime juice powder was determined further. The antioxidant activity was analyzed using the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) method. Results: The results of the study showed that lime juice powder contained flavonoids, saponins, terpenoids, and steroids. The ascorbic acid content was 0.38 mg/100mg. Antioxidant activities revealed strong antioxidant activity with an IC50 value of 32.59 mg/mL, while an IC50 value of ascorbic acid showed 8.57 mg/mL. Conclusions: Lime juice powder has potential as an antioxidant with an IC50 value of lime juice powder being categorized to possess very strong antioxidant activity.